Respuesta :
Represent your unknowns: Let s be the length of one side of the box. The relationship between s and x is s = x-4.
The volume of the box is (length)(width)(height), which here equals the following: V(x) = (x-4)*(x-4)*(x). You may either leave this result as is, or shorten it to V(x) = (x-4)^2*x, or expand (x-4)*(x-4)*(x).
The volume of the box is (length)(width)(height), which here equals the following: V(x) = (x-4)*(x-4)*(x). You may either leave this result as is, or shorten it to V(x) = (x-4)^2*x, or expand (x-4)*(x-4)*(x).
Answer: Our required expression for volume of a box is [tex]x(x-4)^2[/tex]
Step-by-step explanation:
Let the height of the box be 'x'.
Let the length of the box be 'x-4'.
Let the width of the box be 'x-4'.
As we know the formula for volume of a box.
So, the volume of a box is given by
[tex]Volume=Length\times Width\times Height\\\\Volume=(x-4)\times (x-4)\times x\\\\Volume=x(x-4)^2[/tex]
Hence, our required expression for volume of a box is [tex]x(x-4)^2[/tex]